Responsibilities of companies towards employees - Botha, M.M. (My University, 2015)
Central to company law is the promotion of corporate governance. An important question in company law still today is in whose interest the company should be managed. Corporate governance needs to address the entire span of responsibilities to stakeholders of the company such as customers, employees, shareholders, suppliers and the community at large. The promotion of human rights in the application of company law must also take place. This is extremely important given the significant role of enterprises within the social and economic life of the nation. The interests of various stakeholder groups in the context of the corporation as a "social institution" should be enhanced and protected. Because corporations are part of society and the community, like all of us, it is required of them to be socially responsible and have greater accountability to all stakeholders of the company. Although directors must act in the best interests of shareholders collectively they must also consider the interests of other stakeholders. Sustainable relationships with all the relevant stakeholders are thus important. The advancement of social justice is thus important to corporations in that they should take note of the Constitution, labour legislation and company law legislation when social justice issues are dealt with. Employees have become very important stakeholders of companies and their needs should be taken into account in the bigger corporate governance and social responsibility framework.
Keywords: Corporate governance; Corporate law; Corporate social responsibility; Sustainability; Corporate citizenship; Employee participation; Decision-making; Stakeholders; Shareholders; Managerial prerogative; Social justice